(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examines the movement of grains prices in Fatimid Egypt during the period 358-464 AH / 969-1021 AD. This period witnessed the transfer of the Fatimid capital to Egypt and the establishment of the city of Cairo, and the consolidation of the state. This was followed by important economic transformations that had a significant impact on prices, markets, and levels of trade and consumption. The study focuses on analyzing the factors influencing price fluctuations. Among these factors are the agricultural cycle related to the Nile flood, the production of grain, and whether it was organized through the Qanatin system or Istisqa‘, which directly affected the quantities of crops. The study also addresses the proximity of this to issues of storage, hoarding, and scarcity, as well as the role of the commercial and artisanal sectors. The study also clarifies the Fatimid state’s policy toward prices through its institutions, especially the Hisba and the Muhtasib who monitored markets, prevented fraud and monopoly, in addition to state intervention during times of crisis to achieve stability in society. The study concludes that price fluctuations in Fatimid Egypt were not the result of a single factor, but rather the outcome of the interaction of a set of natural, economic, and political factors. The Fatimid state sought to achieve a degree of economic balance through oversight and various administrative procedures